TRENDS IN WORLD PRODUCTION AND TRADE OF MILK, DAIRY PRODUCTS, EGGS AND WOOL - Đorović, Milutin T.; Stevanović, Simo V.; Lazić, Verica M. (Economics of Agriculture, 2011)
This paper presents the regional comparative analysis of major parameters of the world market and trade of milk, dairy products, eggs and wool. The paper particularly analyzes trends and regional differences in the volume, dynamics and structure of production and trade of these products. The regions and countries, largest producers, exporters and importers of above-mentioned products were defined. Based on the previous one, it was found that there are very significant regional differences and that the largest part of production and trade, i.e. exports and imports, is concentrated in the 15 countries, the largest producers and largest exporters and importers of these products. Demonstrated differences and the current state of relations between the observed phenomena are due to many natural, economic and social factors. In considering the relationship trends and degree of influence of these factors on changes of the investigated phenomena, quantitative and qualitative market research methods were used.